2018
DOI: 10.1634/theoncologist.2018-0291
|View full text |Cite
|
Sign up to set email alerts
|

Capecitabine and Temozolomide as a Promising Therapy for Advanced Thymic Atypical Carcinoid

Abstract: Background Thymic atypical carcinoid (TAC) is a rare thymic neuroendocrine tumor that originates in the neuroendocrine system and lacks a standardized treatment. The combination of capecitabine (CAP) and temozolomide (TEM) is associated with an extremely high and long‐lasting response rate in patients with metastatic pancreatic neuroendocrine tumors. However, there is little evidence showing that the CAPTEM regimen is effective for TAC. For patients with unresectable or metastatic atypical carcinoid of the thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
(27 reference statements)
0
6
0
1
Order By: Relevance
“…In the past year, recent studies have reported on the use of CAPTEM in advanced NEN [29][30][31][32][33]. Chatzellis et al (2019) conducted a retrospective analysis of CAPTEM in 79 patients, of which 30 patients (38%) had pNEN and 15 patients had GI NEN primary disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past year, recent studies have reported on the use of CAPTEM in advanced NEN [29][30][31][32][33]. Chatzellis et al (2019) conducted a retrospective analysis of CAPTEM in 79 patients, of which 30 patients (38%) had pNEN and 15 patients had GI NEN primary disease.…”
Section: Discussionmentioning
confidence: 99%
“…Recently published manuscripts have investigated the use of CAPTEM in this population. However, the number of patients available for study remain low [29,32,33,36].…”
Section: Discussionmentioning
confidence: 99%
“…[72][73][74][75] Furthermore, the efficacy of CAPTEM was mostly investigated in GEP-NETs but some evidences suggested a role also in NETs of lung and thymic origin and unknown primary site, irrespective of the treatment line. 61,65,76 We performed a systematic review to assess the efficacy and safety of CAPTEM, including long-term outcomes in patients affected with NENs, with the aim to better clarify the role of this regimen in the therapeutic algorithm of NENs.…”
Section: Introductionmentioning
confidence: 99%
“…Otros estudios como los realizados por Wang X, etal. [14] demuestran que la combinación de capecitabina (CAP) y temozolomida (TEM) llamada también como régimen CAPTEM puede ser efectivo y bien tolerado para el tratamiento de CA de timo, aunque sugieren mayor evidencia para validar su eficacia.…”
Section: Carcinoide Típico Carcinoide Atípico Pacienteunclassified